2018
DOI: 10.1093/jjco/hyy069
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological and molecular differences between right-sided and left-sided colorectal cancer in Japanese patients

Abstract: Comparing RCC with LCRC, RCC is different from LCRC in clinicopathological features, molecular biomarkers and prognostic factors in Japanese colorectal cancer patients. Since the proportions of molecular biomarkers of CRC in this study are different from Western CRCs, further studies are required to clarify the clinicopathological differences between Japanese CRCs and Western CRCs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
20
1
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 44 publications
4
20
1
3
Order By: Relevance
“…In this study, for the eastern China patients, the frequency of RCC was 18.25%, lower than in previous reports from other regions in China such as Shanghai (24.4% and 25.3%), Shantou (36.9%), Tianjin (50.6%), and Guangdong (17.5%), as well as Japan (26.3% and 29.3%) (Xu et al, 2010;Watanabe et al, 2012;Liu et al, 2017;Peng et al, 2017;Qin et al, 2017;Natsume et al, 2018;Guo et al, 2019), whereas the RCC frequency in the United States was as high as 42% (Siegel et al, 2014). This finding indicates that the distribution of RCC in eastern China patients might be different compared to those of other regions in China and Western countries.…”
Section: Discussioncontrasting
confidence: 78%
See 2 more Smart Citations
“…In this study, for the eastern China patients, the frequency of RCC was 18.25%, lower than in previous reports from other regions in China such as Shanghai (24.4% and 25.3%), Shantou (36.9%), Tianjin (50.6%), and Guangdong (17.5%), as well as Japan (26.3% and 29.3%) (Xu et al, 2010;Watanabe et al, 2012;Liu et al, 2017;Peng et al, 2017;Qin et al, 2017;Natsume et al, 2018;Guo et al, 2019), whereas the RCC frequency in the United States was as high as 42% (Siegel et al, 2014). This finding indicates that the distribution of RCC in eastern China patients might be different compared to those of other regions in China and Western countries.…”
Section: Discussioncontrasting
confidence: 78%
“…For the molecular markers in CRC, the mutation rates of MSI-H, KRAS, and NRAS were reported to be 6-15% (Horvat and Stabuc, 2011;Gelsomino et al, 2016;Chang et al, 2017; Samstein and Chan, 2017), 38.5-40% (Natsume et al, 2018), and 1-6% respectively (Downward, 2003). In our study, the frequencies of the MSI-H (6.31%), KRAS (40.15%), and NRAS (3.85%) mutation were in accordance with those in the Western countries and other regions in China, whereas the BRAF (2.29%) mutation was specifically lower.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We also tried to develop a signature to predict CIMP status for stage II and III LCC. However, the prevalence rate of CIMP+ among LCC was only 2.04-6.67% in the training and validation datasets ( Supplementary Table 3), and the statistics showed that the prevalence rate is about 2.67% in several studies (Natsume et al, 2018). There were so few LCC CIMP+ samples that we could not train or validate a signature to predict the CIMP status for LCC samples.…”
Section: Discussionmentioning
confidence: 94%
“…In our study, the KRAS mutation rate was 27.6%, and this rate was similar to that in conventional CRCs. 27 The most frequently mutated gene among NGS cases was TP53. Among the 42 cases of CRCs with enteroblastic marker expression, the TP53 mutation rate was 52.4% (22 of 42) and the p53 overexpression rate was 64.3% (27 of 42).…”
Section: Discussionmentioning
confidence: 99%